KADAR N, P, K TANAH, PERTUMBUHAN DAN PRODUKSI TANAMAN TERUNG UNGU AKIBAT PEMBERIAN PUPUK KANDANG AYAM DAN MULSA PADA TANAH ENTISOL TONDO - Abdul Kadir Paloloang,Ulfiyah A Rajamuddin, Kahar (AGROTEKBIS, 2016)
The objective of the research was to analyze concentration of N, P, and K in soil, growth and yield of purple eggplant (Solanum Melongena L) applied with chicken manure and mulch in Entisol Tondo. This Research was conducted inTondo of Palu, Central Sulawesi from February - May 2015. This research used a Randomized Block Design with two factors i.e. chicken manure and mulch. The chiken manure treatments consisted of with no manure added (control â K0), 10 t ha-1 (K1 ), 20 t ha-1 (K2), and 30 t ha-1(K3). The mulch treatmenst were with no mulch added (M0) and mulch (M1).Â The mulch was applied at 10 t ha-1 covering the whole experimental plot.Â There were eight combinedÂ treatmentsÂ replicates three times, thus in total there wereÂ 24 experimental plots. The results of research indicated that the chicken manure combined with the mulch can improve the concentration of N, P, and K in soil, as well as increase the growth (plant height and leaf number).Â The plant production (fruit number, fruit lenght, and fruit diameter). Â At the rate of 30 t ha-1, the mulch produced the best results on all observed plant variables.